Knowledge and Attitude Towards Euthanasia and Advance Directives amongst Medical Students in a Private Medical College and Hospital at a Metropolitan City of India - P Shruthi; G Sudaakar (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background - Decision making about ‘End of life’ is value-laden with respect to the context of culture andethics. Advanced and improved medical technologies and well qualified health care professionals are alwaystrying to sustain life , sometimes even when there is no hope of recovery .This has led to a need for an endof life decision making legislation more than ever.Euthanasia (Painless or mercy killing) and advance directives are less popular concepts in Indian context asagainst the many of the nations worldwide.Objective- To study the knowledge and attitude of medical students toward euthanasia and advancedirectives.Methodology - 400 medical students were chosen randomly and a cross-sectional descriptive questionnairebased study was conducted administering a pre-tested, semi structured questionnaire to assess theirknowledge and attitude regarding euthanasia and advance directives in a private medical college and hospitalat Chennai. The data collected was statistically analysed using appropriate statistical tools in SPSS software.Results- Female preponderance, 246 (61.5%) was noted in the study with female to male ratio being 1.6:1.76% of them had heard about Euthanasia and 29% of them were aware of the concept of advance directives.61% of them wanted active euthanasia to be legalised. 54% of them believed that this concept may easilybe misused and that was the reason against opting for euthanasia. 34% of them were aware that the mentalhealth act (MHCA) , 2017 promoted advance directive in India.Although none of them had helped anypatient write an advance directive, 77% of them felt that health care providers should always anticipatediscussion about end-of-life issues with the patient.Conclusion- This study concludes that majority of the medical students in teaching medical colleges andhospital had moderate to high level of knowledge of euthanasia and moderate to poor level of knowledgeregarding advance directives.